Developing Ideological Intelligence in Schools: Appreciation and Practice of Pancasila Values through Extracurricular Activities - Hariyanti, Hariyanti; Permady, Gigieh Cahya; Irayanto, Irma; Kartasasmita, Saepudin; Istianah, Anif (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The article's purpose is to describe the idea of ​​actualizing Pancasila values ​​through extracurricular activities to build students' ideological intelligence in school. Data was collected through literature studies using theories relevant to the research theme. In Indonesia, shared values ​​are expressed in Pancasila, which can unite society amidst differences in culture, race, language, religion and political beliefs. Pancasila, as a state ideology, provides orientation, insight, and normative guidelines in all areas of life. Ideological intelligence is needed to appreciate, internalize and apply Pancasila values ​​in life. Ideological intelligence through education is realized in Pancasila, and citizenship education (PPKn) is realized in schools. The revitalization of PPKn as ideological education can be realized in extracurricular activities under the coordination of PPKn teachers, with the advantages of: 1) It provides an ideological learning experience that is fun and easy to digest for students. 2) I am avoiding elements of indoctrination in learning. 3) The entire school community is involved in an open place because ideological intelligence cannot be developed through rhetoric and symbols.